Perlindungan Hak Konsumen dalam Layanan e-Commerce melalui Sistem COD: Elaborasi dalam Kerangka Hukum Islam - Illa Nabillah; Euis Fajriyah; Firdaus (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2023)
Online buying and selling are a form of buying and selling activity that has its own characteristics, which utilizes the internet. Such conditions are very favorable to consumers on the one hand, because they provide an opportunity to have many choices in obtaining goods and services. After all, violations of consumer rights are possible. Therefore, it is necessary to protect consumer rights in buying and selling online. This study aims to analyze the protection of consumer rights in e-Commerce services through the COD system at JNE Galagamba-Ciwaringin-Cirebon and its elaboration within the framework of Islamic law. This research is a qualitative research with data collection using observation techniques, documentation, and interviews. Protection of consumer rights in e-commerce transactions through the COD system carried out at JNE Galagamba-Ciwaringin-Cirebon is basically in accordance with Islamic law because there are khiyar rights, namely the return of goods and funds.  delivery of goods with the COD system where it has been carried out according to the procedure for customers who order online.